2008
DOI: 10.1590/s1516-35982008000300019
|View full text |Cite
|
Sign up to set email alerts
|

Resíduo proveniente do beneficiamento do feijão (Phaseolus vulgaris L.) em rações para vacas em lactação: consumo, digestibilidade, produção e composição do leite e eficiência de alimentação

Abstract: Este trabalho foi conduzido com o objetivo de avaliar o efeito da substituição do farelo de soja pelo resíduo de feijão comum (Phaseolus vulgaris L.) em rações para vacas em lactação sobre as seguintes variáveis: consumos e digestibilidades totais aparentes dos nutrientes, produção e composição do leite e eficiência alimentar. Foram utilizadas 12 vacas da raça holandesa, distribuídas em três quadrados latinos 4 <FONT FACE=Symbol>´</FONT> 4, balanceados. Os animais receberam rações completas ofertad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
(12 reference statements)
2
9
0
2
Order By: Relevance
“…Apresenta em média uma composição de 89% matéria seca (MS), 23% proteína bruta (PB), 21% de fibra em detergente neutro (FDN), 9% de fibra em detergente ácido (FDA), 7,81% de proteína insolúvel em detergente neutro (PIDN), 1,51% de proteína insolúvel em detergente ácido (PIDA), 1,67% de extrato etéreo (EE), 5,11% de matéria mineral (MM), 1,4% de lignina, 72,61% de carboidratos totais (CT) e 34,9% de carboidratos não-fibrosos (CNF) (Magalhães et al, 2008;Marcondes et al, 2009;Azevêdo et al, 2011).…”
Section: Discussionunclassified
“…Apresenta em média uma composição de 89% matéria seca (MS), 23% proteína bruta (PB), 21% de fibra em detergente neutro (FDN), 9% de fibra em detergente ácido (FDA), 7,81% de proteína insolúvel em detergente neutro (PIDN), 1,51% de proteína insolúvel em detergente ácido (PIDA), 1,67% de extrato etéreo (EE), 5,11% de matéria mineral (MM), 1,4% de lignina, 72,61% de carboidratos totais (CT) e 34,9% de carboidratos não-fibrosos (CNF) (Magalhães et al, 2008;Marcondes et al, 2009;Azevêdo et al, 2011).…”
Section: Discussionunclassified
“…Likewise, Magalhães et al (2008) evaluated starea and common-bean residue in steers diets and also observed a decrease in the EE intake of the animals fed the highest levels of the commonbean residue. A study conducted by Ferro (2014) to evaluate the use of common-bean residue in sheep feeding demonstrated lower EE intake by sheep fed the highest levels of inclusion of commonbean residue, and this reduction of EE intake was attributed to the lower concentration of this nutrient in the common-bean residue when it substituted the cottonseed cake as it was included in diets for feedlot sheep.…”
Section: Resultsmentioning
confidence: 91%
“…When expressed in %BW, the DM intake by the sheep decreased linearly (P<0.05) with the inclusion of the common-bean residue in the experimental diets (Table 4), with a reduction of 0.01 percentage units with every 1.0% of inclusion of the residue in the diets. Likewise, Magalhães et al (2008) substituted soybean meal for common-bean residue at 0, 5.2, 10.4, and 15.6% of the DM of lactating cow diets and observed a decrease in the intakes of DM, OM, CP, and EE. According to these authors, the low palatability of the common-bean residue as a consequence of the presence of tannins, and the increased dustiness of the concentrates, which, when in contact with saliva, form a pasty material that complicates chewing, contributed to these results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] already indicated the inclusion 20% and 10% in diets for dairy and beef cattle. [8] evaluated the inclusion of 0%, 13%, 26% and 39% in concentrates for lactating cows and found that the inclusion of beans resulted in the reduction of milk production of the animals.…”
Section: Introductionmentioning
confidence: 99%